Analisis Faktor dalam Keputusan Perusahaan Kecil dan Menengah Memilih Penyedia Layanan Billboard (Studi pada Pilar Advertising) - Citra Wanodya Rahmahani; Teofilus Teofilus; Natalia Christiani (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to identify and describe the factors that shape the purchase decisions of small and medium-sized enterprises in selecting billboard service providers. The study is motivated by the risks, barriers, and uncertainties associated with using billboards as an outdoor advertising medium, which encourage small and medium-sized enterprises to conduct selective evaluations of service providers. Employing a descriptive quantitative approach, data were collected from decision-makers at 56 small and medium-sized enterprises that are clients of Pilar Advertising in the Kediri Raya and analyzed using Exploratory Factor Analysis (EFA). The results reveal nine factors influencing purchase decisions: price attractiveness, after-sales service, product attributes, service flexibility, information sources, trustworthiness, relationship quality, service adaptability, and relationship commitment, with price attractiveness emerging as the most dominant factor, reflecting the sensitivity of small and medium-sized enterprises to economic value considerations. This study contributes theoretically to a deeper understanding of organizational purchase decisions in the outdoor advertising industry and extends the application of the Theory of Trying within an organizational context. Practically, the findings provide insights for Pilar Advertising to better align its service strategies with client needs. The study is limited by its localized sample and the absence of external organizational decision-making factors in the research model; therefore, future research is recommended to expand the geographical scope, incorporate external variables, and conduct confirmatory analyses to validate the stability of the identified factor constructs.